Paradigma Baru Pendidikan Agama Islam Dan Pendidikan Islam (Tinjauan Epistemologi) - Misnan (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
This paper presents two terms that while there is a difference that is Islamic Religious Education and Islamic Education. To see the two terms the authors review it from two interrelated aspects of epistemology as the theory of knowledge and content or material aspects that is one of the important points in the understanding of the curriculum. Meanwhile, in terms of epistemology, Islamic Religious Education is more inclined towards the application in Islamic education. Medium Islamic education speaks in the level of sources, theories, principles that memorandum become the forerunner of Islamic Religious Education itself. In terms of content or material, basically between Islamic Education and Islamic Education as in the view of epistemology, there is no significant difference, where the term contained in Islamic Religious Education is aqidah, worship, and morals, essence is the introduction to Allah swt., human potential and function, and morals.